Connexin43 in retinal injury and disease. (March 2016) - Danesh-Meyer, Helen V.; Zhang, Jie; Acosta, Monica L.; Rupenthal, Ilva D.; Green, Colin R.
Abstract: Gap junctions are specialized cell-to-cell contacts that allow the direct transfer of small molecules between cells. A single gap junction channel consists of two hemichannels, or connexons, each of which is composed of six connexin protein subunits. Connexin43 is the most ubiquitously expressed isoform of the connexin family and in the retina it is prevalent in astrocytes, Müller cells, microglia, retinal pigment epithelium and endothelial cells. Prior to docking with a neighboring cell, Connexin43 hemichannels have a low open probability as open channels constitute a large, relatively non-specific membrane pore. However, with injury and disease Connexin43 upregulation and hemichannel opening has been implicated in all aspects of secondary damage, especially glial cell activation, edema and loss of vascular integrity, leading to neuronal death. We here review gap junctions and their roles in the retina, and then focus in on Connexin43 gap junction channels in injury and disease. In particular, the effect of pathological opening of gap junction hemichannels is described, and hemichannel mediated loss of vascular integrity explained. This latter phenomenon underlies retinal pigment epithelium loss and is a common feature in several retinal diseases. Finally, Connexin43 channel roles in a number of retinal diseases including macular degeneration, glaucoma and diabetic retinopathy are considered, along with results from related animal models. A final section describes gap junction channel modulation and the ocular delivery of potential therapeutic molecules. Highlights: Connexin43 gap junctions link a number of retinal cells including astrocytes, microglia and vascular endothelium. Upregulation of Connexin43 expression occurs within hours of injury and contributes to secondary damage and vision loss. Connexin43 expression is increased in both acute and chronic retinal diseases. Transient blockade of Connexin43 channels reduces inflammation and edema, prevents vascular leak and protects neurons.